2023
DOI: 10.1130/ges02315.1
|View full text |Cite
|
Sign up to set email alerts
|

Tectonics, geochronology, and petrology of the Walker Top Granite, Appalachian Inner Piedmont, North Carolina (USA): Implications for Acadian and Neoacadian orogenesis

Abstract: The Walker Top Granite (here formally named) is a peraluminous megacrystic granite that occurs in the Cat Square terrane, Inner Piedmont, part of the southern Appalachian Acadian-Neoacadian deformational and metamorphic core. The granite occurs as disconnected concordant to semi-concordant plutons in migmatitic, sillimanite zone rocks of the Brindle Creek thrust sheet. Locally garnet-bearing, the Walker Top Granite contains blocky alkali feldspar megacrysts 1–10 cm long in a groundmass of muscovite-biotite-qua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Hibbard et al (2010) and Hibbard and Karabinos (2013) suggested that this first-order along-strike transition took place near the New York Promontory, where the Devonian clastic wedge is thickest (Faill et al, 1985). Furthermore, there might also be a change of Acadian-Neoacadian subduction polarity near the southern end of the New York Promontory, with the Laurentian margin obliquely subducted beneath the Carolinia in the central and southern Appalachians (Hatcher & Merschat, 2006;Merschat et al, 2023). The lack of significant Acadian crustal shortening and clastic wedge formation in the central and southern Appalachians suggests that accreted terranes were juxtaposed with Laurentia via transpression (e.g., Dennis et al, 2007), without significant crustal shortening perpendicular to the orogen, as shown in Figure 6f.…”
Section: The Acadian-neoacadian Orogenymentioning
confidence: 99%
“…Hibbard et al (2010) and Hibbard and Karabinos (2013) suggested that this first-order along-strike transition took place near the New York Promontory, where the Devonian clastic wedge is thickest (Faill et al, 1985). Furthermore, there might also be a change of Acadian-Neoacadian subduction polarity near the southern end of the New York Promontory, with the Laurentian margin obliquely subducted beneath the Carolinia in the central and southern Appalachians (Hatcher & Merschat, 2006;Merschat et al, 2023). The lack of significant Acadian crustal shortening and clastic wedge formation in the central and southern Appalachians suggests that accreted terranes were juxtaposed with Laurentia via transpression (e.g., Dennis et al, 2007), without significant crustal shortening perpendicular to the orogen, as shown in Figure 6f.…”
Section: The Acadian-neoacadian Orogenymentioning
confidence: 99%